Risk Factors for Proximal Junctional Kyphosis Associated With Dual-rod Growing-rod Surgery for Early-onset Scoliosis. Issue 8 (October 2016) - Watanabe, Kota; Uno, Koki; Suzuki, Teppei; Kawakami, Noriaki; Tsuji, Taichi; Yanagida, Haruhisa; Ito, Manabu; Hirano, Toru; Yamazaki, Ken; Minami, Shohei; Taneichi, Hiroshi; Imagama, Shiro; et al.
Abstract : Study Design: A retrospective, multicenter study. Objective: To identify risk factors for proximal junctional kyphosis (PJK) when treating early-onset scoliosis (EOS) with dual-rod growing-rod (GR) procedure. Summary of Background Data: The risk factors for PJK associated with GR treatment for EOS have not been adequately studied. Methods: We evaluated clinical and radiographic results from 88 patients with EOS who underwent dual-rod GR surgery in 12 spine centers in Japan. The mean age at the time of the initial surgery was 6.5±2.2 years (range, 1.5–9.8 y), and the mean follow-up period was 3.9±2.6 years (range, 2.0–12.0 y). Risk factors for PJK were analyzed by binomial multiple logistic regression analysis. The potential factors analyzed were sex, etiology, age, the number of rod-lengthening procedures, coronal and sagittal parameters on radiographs, the type of foundation (pedicle screws or hooks), the uppermost level of the proximal foundation, and the lowermost level of the distal foundation. Results: PJK developed in 23 patients (26%); in 19 of these, the proximal foundation became dislodged following PJK. Binomial multiple logistic regression analysis identified the following significant independent risk factors for PJK: a lower instrumented vertebra at or cranial to L3 [odds ratio (OR), 3.32], a proximal thoracic scoliosis of ≥40 degrees (OR, 2.95), and a main thoracic kyphosis of ≥60 degrees (OR, 5.08). Conclusions: The significant independent risk factors for PJK during dual-rod GR treatment for EOS were a lower instrumented vertebra at or cranial to L3, a proximal thoracic scoliosis of ≥40 degrees, and a main thoracic kyphosis of ≥60 degrees.